The effects of triiodothyronine on rat testis - Oner, Jale; Oner, Hakan; Colakoglu, Neriman; Kukner, Aysel; Ozan, Enver (Springer, 2006)
The aim of present study was to investigate the effects of 3,3',5-triiodothyronine (T(3)) on rat testis both morphometrically and immunohistochemically with determining of insulin-like growth factor I (IGF-I) expression. Adult male Wistar-albino rats used in the study were divided into two groups; control and T(3)-treated groups. After T(3) treatment there was observed to be a decrease in testicular weights, diameters of seminiferous tubules and the number of sertoli cells, and an increase in the number of leydig cells (P < 0.05). Some of the seminiferous tubule lumens of T(3) administrated rats had cellular debris. IGF-I was localized in sertoli cells, late spermatids and leydig cells of all groups. IGF-I immunoreactivity in T(3) treated rats was higher than in controls in all stages of the cycle of rat seminiferous epithelium, but the staining intensity of leydig cells were similar in both groups. In conclusion, the present results suggest that T(3) may modulate the testicular function by affecting IGF-I activity at the gonadal level.
Keywords: IGF-I; T(3); testis